Development of a Smart Home Control System - Okemiri, H.A; Chukwu, SC; Nwachi, E. Uche; Oketa, K.C; Eze, SC; V.I. Aniji,; A.Y. Idris, (International Journal of Computer Sciences and Engineering, 2021)
In the past, before the advancement of computer technology, the control of home appliances was done manually at their various locations by a user. This kind of control has shortfalls such as lack of control of home appliances remotely and displeasing stress and discomfort to home appliance users, to mention but a few. However, these problems lead to this project research which is on the design and implementation of a Smart Home Control System, with the following objectives; to solve problems involving the lack of ease and comfort in the use and control of home appliances, provide help and support for home appliance users and generally bring technology and automation into various home appliances and devices. This research work followed the structured project design methodology with tools such as the Arduino Uno microcontroller, NodeMCU WIFI Module, Ethernet + WIFI Router, Smartphone with Android 2.3+, Arduino IDE platform with C++ programming language. The result of this research is to prove that the control of home appliances can be done wirelessly. The system when implemented, would be able to control electrical appliances and devices in the home with a relatively low cost design, user-friendly interface and ease of installation.